Mechanisms of As, Cd, Pb, and Zn hyperaccumulation by plants and their effects on soil microbiome in the rhizosphere - Asare, Michael O.; Száková, Jiřina; Tlustoš, Pavel (Frontiers in Environmental Science, 2023)
Excess potentially toxic elements (PTEs), including arsenic (As), cadmium (Cd), lead (Pb), and zinc (Zn), above permissible limits in the environment, have detrimental effects on trophic levels. Hence, imperative to devise advertent measures to address this situation, especially in the soil ecosystem: the major reservoir of many PTEs. Using aerial plant parts (shoot) to accumulate As, Cd, Pb, and Zn - hyperaccumulators are considered a permanent approach to PTE removal from soils. This communication expatiated the principles that govern the hyperaccumulation of plants growing on As, Cd, Pb, and Zn-contaminated soils. The contribution of soil microbial communities during hyperaccumulation is well-elaborated to support the preference for this remediation approach. The study confirms a flow direction involving PTE uptake – translocation – tolerance – detoxification by hyperaccumulators. Rhizosphere microbes exhibit a direct preference for specific hyperaccumulators, which is associated with root exudations, while the resultant formation of chelates and solubility of PTEs, with soil physicochemical properties, including pH and redox potential, promote uptake. Different compartments of plants possess specialized transporter proteins and gene expressions capable of influx and efflux of PTEs by hyperaccumulators. After PTE uptake, many hyperaccumulators undergo cellular secretion of chelates supported by enzymatic catalysis and high transport systems with the ability to form complexes as tolerance and detoxification mechanisms. The benefits of combining hyperaccumulators with beneficial microbes such as endophytes and other rhizosphere microbes for PTE removal from soils are vital in enhancing plant survival and growth, minimizing metal toxicity, and supplying nutrients. Inoculation of suitable rhizosphere microbes can promote efficient cleaning of PTEs contaminated sites utilizing hyperaccumulator plants.